1979
DOI: 10.1002/mpo.2950060207
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal lymphocyte function in childhood leukemia

Abstract: (1 0 f 3% lymphocytes, 88 f 4% lymphoblasts and 18 k 28% T cells) had a significantly lower response to PHA on these days (13,609 * 5,568 cpm).Six of the ten high-WBC patients had a delayed peak response on the sixth or seventh day of culture. This abnormal response to PHA is similar to that which has been described in patients with chronic lymphatic leukemia and is at least partially due to the dilution of a normal lymphocyte population by the proliferation of a population of non-PHA-responsive lymphoblasts.T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1983
1983
1983
1983

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…It is of interest that all of the patients mentioned died after 1 6 months, without obtaining remission. These pa tients seem to be analogous to those described by Zusnum and Nesbit [18], i.e. to those with flat PHA dose and time response curve and simultaneous short survival period, which was suggested to correspond to their truly immunological abnormality.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…It is of interest that all of the patients mentioned died after 1 6 months, without obtaining remission. These pa tients seem to be analogous to those described by Zusnum and Nesbit [18], i.e. to those with flat PHA dose and time response curve and simultaneous short survival period, which was suggested to correspond to their truly immunological abnormality.…”
Section: Discussionmentioning
confidence: 76%
“…So it seems doubtful that the observed high amount of Ml cells was due to the proliferation of self-proliferating leukemic cells. Previous studies in dicate that the peripheral lymphocyte response to PHA in children with ALL and high initial WBC docs not reach its normal value until 96 h of culturing [18]. The nature of the delay remained obscure, although it was suggested that it may be due to the dilution of a normal lymphocyte population by the circulating non-PHA-responsive lymphoblasts [10,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation